Local delivery of allogeneic bone marrow and adipose tissue‐derived mesenchymal stromal cells for cutaneous wound healing in a porcine model. (18th February 2013) - Hanson, Summer E.; Kleinbeck, Kyle R.; Cantu, David; Kim, Jaeyhup; Bentz, Michael L.; Faucher, Lee D.; Kao, W. John; Hematti, Peiman
Abstract: Wound healing remains a major challenge in modern medicine. Bone marrow‐ (BM) and adipose tissue‐ (AT) derived mesenchymal stromal/stem cells (MSCs) are of great interest for tissue reconstruction due to their unique immunological properties and regenerative potential. The purpose of this study was to characterize BM and AT‐MSCs and evaluate their effect when administered in a porcine wound model. MSCs were derived from male Göttingen Minipigs and characterized according to established criteria. Allogeneic BM‐ or AT‐MSCs were administered intradermally (1 x 10 6 cells) into partial‐thickness wounds created on female animals, and covered with Vaseline® gauze or fibrin in a randomized pattern. Animals were euthanized at 7, 10, 14 and 21 days. Tissues were analyzed visually for healing and by microscopic examination for epidermal development and remodelling. Polymerase chain reaction (PCR) was used to detect the presence of male DNA in the specimens. All wounds were healed by 14 days. MSC‐injected wounds were associated with improved appearance and faster re‐epithelialization compared to saline controls. Evaluation of rete ridge depth and architecture showed that MSC treatment promoted a faster rate of epidermal maturation. Male DNA was detected in all samples at days 7 and 10, suggesting the presence of MSCs. We showed the safety, feasibility and potential efficacy of local injection of allogeneic BM‐ and AT‐MSCs for treatment of wounds in a preclinical model. Our data in this large animal model support the potential use of BM‐ and AT‐MSC for treatment of cutaneous wounds through modulation of healing and epithelialization. Copyright © 2013 John Wiley & Sons, Ltd.